2005
DOI: 10.1002/cbf.1270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the blockade of high voltage‐activated calcium channels on in vitro pineal melatonin synthesis

Abstract: The presence of high voltage-activated calcium channels in the rat pineal gland is well known. However, their role in pineal metabolism is not completely understood and is even controversial. Better to understand this matter, we investigated the effects of L-, N- or P/Q-type calcium channel blockers (nifedipine, omega-conotoxin GVIA, omega-agatoxin IVA, respectively) on melatonin content and arylalkylamine-N-acetyltransferase activity of denervated rat pineal glands kept for 48 h in culture and stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Second, tetrodotoxin, a blocker of Na v channels, does not abolish spon- taneous firing of AP in rat pinealocytes (27), suggesting a role of Ca v channels in spike depolarization. Consistent with this hypothesis, it has been reported that rat and chicken pineal cells express L-, P/Q, and N-type Ca v channels (17,18,35,36). Unpublished RNA transcriptome profiling by RNA-Seq indicates that relative expression of mRNA encoding these channels in rat pinealocytes is L-type Ͼ T-type Ͼ Ͼ P/Q-type and Ϸ R-type channels (Klein, D. C., unpublished data).…”
Section: Spontaneous Electrical Activity In Resting Cellsmentioning
confidence: 57%
See 1 more Smart Citation
“…Second, tetrodotoxin, a blocker of Na v channels, does not abolish spon- taneous firing of AP in rat pinealocytes (27), suggesting a role of Ca v channels in spike depolarization. Consistent with this hypothesis, it has been reported that rat and chicken pineal cells express L-, P/Q, and N-type Ca v channels (17,18,35,36). Unpublished RNA transcriptome profiling by RNA-Seq indicates that relative expression of mRNA encoding these channels in rat pinealocytes is L-type Ͼ T-type Ͼ Ͼ P/Q-type and Ϸ R-type channels (Klein, D. C., unpublished data).…”
Section: Spontaneous Electrical Activity In Resting Cellsmentioning
confidence: 57%
“…These cells express numerous plasma membrane channels as revealed by electrophysiological studies, including voltage-gated Ca 2ϩ (Ca v ) and voltage-gated Na ϩ (Na v ) channels, two types of Ca 2ϩ -controlled K ϩ (K Ca ) channels, and at least two types of voltage-activated K ϩ channels (7,(15)(16)(17)(18)(19)(20)(21). Rat pinealocytes fire action potentials (AP) spontaneously, with the firing rate being low during the day time and high during the night time (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…AANAT activity was measured by a radiometric assay (Afeche et al, 2006;Deguchi and Axelrod, 1972;Parfitt et al, 1975). Briefly, 100μl of 0.1M sodium phosphate buffer, pH 6.8, containing 40mM tryptamine and [ 3 H]-acetyl coenzyme A (2mM, final specific activity = 4mCi/mmol) were added to a microcentrifuge tube containing one gland kept at 4°C.…”
Section: Aanat Activity Determinationmentioning
confidence: 99%
“…Experiment 1: Standard pineal gland culture Pineal glands were cultured as described previously (Afeche et al, 2006). Briefly after decapitation, rat pineal glands were isolated and immediately placed in ice-cold BGJb (FittonJackson Modification) medium with phenol red, modified by the addition of bovine serum albumin (BSA; 1mg/mL), 2mM glutamine, 0.1mg/mL ascorbic acid and penicillin (100U/mL)-streptomycin (100μg/mL) (Gibco.…”
Section: Experimental Designmentioning
confidence: 99%
“…Moreover, high voltage-activated calcium channels are also present in the rat pineal gland (Afeche et al, 2006;Chik et al, 1995Chik et al, , 1997Chin et al, 1992) and these seem to be activated either by acetylcholine or norepinephrine (Afeche et al, 2006;Darvish and Russell, 1998;Letz et al, 1997). We have recently reported that the blockade of L-type calcium channel with nifedipine, a specific L-type calcium channel antagonist belonging to dihydropyridine class, reduced melatonin synthesis (Afeche et al, 2006), but the mechanisms involved were not resolved.…”
Section: Introductionmentioning
confidence: 98%